The Use Of Audio Visual Media In Learning To Listen To The Pulau Si Mardan Theater Performance In Tanjungbalai City At Sisingamangaraja Tanjungbalai High School - Anastasia Hotmauli Sinaga; Johar Amir; Janri S. Simanungkalit (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
The aim of the research is to describe the effectiveness of using audio-visual media in learning to listen to Mardan Island theater performances at Sisingamangaraja Tanjung Balai High School, as well as explaining the components that support the effectiveness of using audio-visual media in learning to listen to Mardan Island theater performances. This research method uses qualitative and descriptive qualitative research methods, where the data used is secondary data that has been processed for analysis and description into research results. The data used is very effective in understanding and explaining problems related to learning to listen to theater stories through audio-visual by carrying out data collection techniques through observations and interviews conducted with Sisingamangaraja Tanjung Balai High School students, where the results of observations and interviews were carried out by submitting open questions to students Sisingamangaraja High School regarding the use of audio-visual media by listening to Marjan Island theater stories. The results of the research found in the Si Mardan Island theater performance were that audio visual media was very effective in learning to listen to Si Marjan Island dramas, where the use of audio visuals was very effective because the use of audio visuals could help understand the meaning of the story and the message of the Si Marjan Island story in depth, and can solve problems by evaluating and analyzing the elements of the Pulau Si Marjan story through audio visual media by being able to solve problems related to the discussion of the Pulau Si Marjan story, as well as from solving existing problems, then students can identify problems and moral messages, and conclude What moral message does the story convey to students? The results of this research can be seen from the results of interviews with several Sisingamangaraja High School students, as well as quantitative test results from several students at Sisingamangaraja High School. The material test carried out at the end of the lesson showed that the students' literacy scores were very satisfactory, because the students were able to translate, analyze and evaluate the story, as well as the moral message contained in the Pulau Si Marjan theater story. Based on the research results, it can be concluded that the use of audio-visual media in learning to listen to the Si Mardan Island theater at Sisingamangaraja Tanjung Balai High School is very effective, both in attracting students' attention and helping students understand the learning material of listening to the story of the Si Mardan Island theater through the use of audio-visual media effectively. explain and describe the theme, story content and moral message with.